Systematic adjustment strategy of a nonlinear beam generator for high-energy orbit. (1st March 2022) - Huang, Yao; Zhao, Zelong; Liu, Weiqun
Highlights: A systematic adjustment strategy for high-energy orbit of a nonlinear generator is proposed. The different possible steady-state behaviors of the nonlinear beam oscillator are investigated. Several typical cases are summarized. A maximum increase on the harvested power up to two orders of magnitude can be achieved. Experimental validation is performed based on a nonlinear piezoelectric buckled beam generator. Abstract: It is a promising technology to effectively extract energy from the environmental vibrations. Recent studies have indicated that nonlinear generators can generally overcome many significant disadvantages of linear generators stemming from the narrow bandwidth and the low power density. Nevertheless, owing to multiple steady-state behaviors of the nonlinear system, high-energy orbits are coexisting with low-energy orbits on a major portion of the operating frequency range. Nothing but the large amplitudes of oscillations on the high-energy orbit can contribute significantly to energy harvesting, which cannot be achieved automatically. Thus, an systematic adjustment strategy is proposed by slow structural characteristics matching technique or extra energy impact technique or a combination of the two for the higher-energy orbit under variable vibration excitations. Following the analytical orbits obtained from the theory, it is experimentally verified that the buckled beam generator can generate two orders of magnitude larger power with the adjustment strategy compared to the original power. Moreover, the consumed energy is negligible and enough to get rid of the high power regulator. The studied adjustment strategy and results of this work can provide valuable guidelines for wider applications of nonlinear generators, especially under variable vibration excitations.